Strategi Pemasaran Layanan Perpustakaan dalam Menghadapi Pandemi Covid-19 - Leady Yurmeli Br Barus; Nining Sudiar (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
At the beginning of 2020, there was a Pandemic, namely Covid-19 which had a lot of impact on normal activities carried out by humans, including library activities that had been running so far. Library activities are manually stopped to avoid close contact with users as an action in preventing and transmitting Covid19, besides that libraries need a marketing strategy to be seen as one of the bases used in compiling overall library planning. This article aims to get an overview of the library service marketing strategy in the face of the Covid-19 pandemic. The research method used is through a literature study of scientific concepts related to library science. The marketing strategy for library services is required to be able to provide changes during this Covid-19 pandemic for the better.